Study on Weight of Cerebellum in Bangladeshi Cadaver (Bangladesh Journal of Anatomy, 2015)
Context: Cerebellum is involved in the maintenance of balance and posture, coordination of voluntary movements, motor learning and cognitive functions. The weight of the human cerebellum at birth is only a fraction of the adult weight then weight increases up to certain age and decreases in old age. So, the present study was performed to observe the weight of the cerebellum in different age groups of Bangladeshi cadaver which will serve as a baseline data for clinicians regarding management of neurological disorders in our country.Materials and Methods: A cross sectional, analytical type of study was carried out in the department of Anatomy, Mymensingh Medical College, Mymensingh from April’ 2009 to September ’2009. A total of 63 cerebellums were collected from unclaimed Bangladeshi cadavers aged between 5 to 60 years and from dead fetuses obtained from caesarian section aged between 34 wks to 41 wks of gestation. The collected sample was grouped into three age groups like Group A (34 to 41 weeks of gestation), Group B (5 to 30 years) and Group C (31 to 60 years). Each cerebellum was weighed by means of a scientific balance.Results: The mean (±SD) weight was 17.91±3.05 gm in Group A, 125.91±15.24 gm in Group B and 115.29±18.06 gm in Group C.Conclusion: The present study shows that the mean weight of the cerebellum increases with age upto certain level then slightly decreases in the late age.Bangladesh J. Anat. 2015; 13(1) : 23-26